Memastikan Perhotelan Berkelanjutan: Studi Kasus Tentang Tata Kelola Kesehatan dan Keselamatan Kerja di Ros In Hotel - Nugraha, Ogi Nanda Raka Ade Candra; Sari, Risnawati Ambar; Riyanto, Vava Rosian Aurielta; Isnaini, Meilia; Ifriana, Fesi (ASEAN Journal on Hospitality and Tourism, 2024)
Workplace accidents often stem from worker negligence, human error, and insufficient management, including substandard occupational health and safety measures. Case studies, a common qualitative research method, utilize interviews and observations for primary data collection. In a specific case study at Hotel Ros-In, Yogyakarta, the Human Resources Manager was the key informant, participating in a 60-minute interview with three sub-themes: Covid-19 Post-Pandemic Regulation, Occupational Health and Safety, and Environmental Health. During the interview, Ros-In Hotel exhibited a robust commitment to complying with Ministry of Tourism and Creative Economy guidelines on hygiene, health, safety, and environmental sustainability. In the industrial sector, effective health and safety governance is crucial for maintaining consumer confidence and ensuring facilities meet stringent standards, protecting both consumers and workers. Strong safety protocols actively reduce workplace accidents and occupational diseases, fostering a safer work environment. This commitment not only benefits employees' well-being but enhances the company's overall reputation. Companies like Ros-In Hotel, through adherence to regulatory guidelines and robust safety measures, play a vital role in establishing a secure working atmosphere, instilling confidence in consumers and the broader community.